2-Chlorophenol Degradation via Photo-Fenton Reaction employing Zero Valent Iron Nanoparticles - Ortiz de la Plata, Guadalupe Beatriz (2012)
In the present work the influence of various factors on the degradation of 2-chlorophenol (2-CP) via heterogeneous photo Fenton reaction using zero valent iron (ZVI) nanoparticles as a source of iron was studied. The results were compared with those obtained using goethite as a reservoir of iron. During the study the pH, catalyst loading and the level of irradiation were varied. In the results it can be observed: (i) a high dependence of the working pH, rendering better results as pH decreases, (ii) a great improvement in conversion by applying radiation, as compared with the data obtained under dark conditions, (iii) an interesting non-linearity between conversion and catalyst loading, which can be partially explained by estimating the average radiation absorption available in the reactor for different catalyst loads, using the information given by the optical properties of ZVI.